PERAN TRADE ANALYSIS FOR FLAURA AND FAUNA IN COMMERCE (TRAFFIC) DALAM MENCEGAH PERDAGANGAN SATWA ILEGAL DIANTARA NEGARA-NEGARA ASEAN TAHUN 2019-2020 - Prabudhi, Oriel Muharromy; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Illegal wildlife trade threatens the survival of certain species and poses a risk to human welfare and health. This issue has become a global concern, especially in Southeast Asia, which requires the help and support of the Trade Analysis for Flaura and Fauna in Commerce (TRAFFIC) organization. How TRAFFIC implements the TRAFFIC program to combat the problem of illegal wildlife trade is discussed in depth in this study. The research method used is qualitative with data collection techniques through literature studies. This research uses a pluralism perspective to explain how non- state actors can have a role in collaborative action at the national and international levels. Non-Governmental Organization theory is used to analyze the implementation of TRAFFIC's role function as an NGO in preventing illegal wildlife trade. The results showed that TRAFFIC performs the functions of advocacy, service provider, facilitator, and local capacity building in preventing illegal wildlife trade. Concrete steps taken by reducing consumer demand, strengthening law enforcement, and raising awareness of the dangers of wildlife trade. There has been a decrease in cases for the prevention of illegal wildlife trade since 2019-2020. Keywords: Illegal Wildlife Trade, TRAFFIC, NGO, Southeast Asia